The Right to Equality at the Dissolution of a Marriage in Uganda. (25th May 2019) - Mujuzi, Jamil Ddamulira
Abstract: Article 31(1) of the Constitution of Uganda provides that '[a] man and a woman are entitled to marry only if they are each of the age of eighteen years and above and are entitled at that age – (a) to found a family; and; (b) to equal rights at and in marriage, during marriage, and at its dissolution.' During the making of the Ugandan constitution, some Constituent Assembly delegates argued that the constitution should expressly provide that at the dissolution of a marriage, spouses should have a right to equitable distribution of property. After a heated debate, this proposal was not included in the Constitution. However, jurisprudence emanating from Ugandan courts shows that courts have interpreted Article 31(1) to mean that at the dissolution of a marriage, spouses have a right to equitable distribution of property. A similar approach has been followed in some African countries. The purposes of this article are to demonstrate the drafting history of Article 31(1) and to discuss jurisprudence from Ugandan courts on Article 31(1). The author also demonstrates how courts in other African countries have dealt with the issue of distribution of property when a marriage is dissolved.